A study on electronic procurement's user satisfaction - Wan Nurulhidayah, Wan Samsudin (2014)
This study examines the direct relationship between perceived ease of use, perceived usefulness, top management support, vendor assurance, vendor responsivenss and user‟s satisfaction. A total of 450 questionnaires were disributed to participants who had agreed to participate in this study. However, only 312 questionnaire were usable for further analyses. Hypotheses for direct effect were tested using multiple regression analyses. Results showed that all variable tested in this study, namely perceived ease of use, perceived usefulness, top management support, vendor assurance, vendor responsiveness were significantly positively associated with user's satisfaction. Implications of the findings, potential limitations, and directions for future research are discussed